Addressing Multinutrient Deficiency in crops using customized fertilizer - Dass, Anchal; Jinger, Dinesh; Kaur, Ramanjit; Kumar, S Vijaya; Kumari, Kavita (Indian Farming, 2017)
The customized fertilizer which contain both macro and micro nutrients now manufactured in India are available for use in agriculture. At several places, yield increase exceeding 100% due to use of CF over traditional fertilizers has been reported by several workers. Thus region-agro-climate- and cropspecific CF should be offered to the farmers to remediate nutrient deficiencies particularly secondary and micronutrients for better crop response and higher productivity.